Fatwa of the Indonesian Council of Ulama (MUI) Number 11 of 2012 on the Status of Children Born Out of Wedlock: An Analysis of Maqasid Al-Shari’ah Using Jasser Auda's System Approach - Sanjaya, Edi; Hasanah, Idaul; Zakaria, Soni; Zuhri, Muhammad Arif (Sakina: Journal of Family Studies, 2024)
This research examines the status of children born out of wedlock under Fatwa No. 11 of 2012 issued by the Indonesian Council of Ulama (MUI) and analyzes it through the lens of Maqasid Shariah using Jasser Auda’s system approach. Employing a qualitative method with descriptive analysis and a philosophical approach to Islamic law, the study focuses on ensuring the welfare and rights of children born out of wedlock. It highlights the importance of scholars' cognitive construction, such as Ibn Taimiyyah’s views, and the integration of arguments to prevent methodological reductionism. Emphasis is placed on protecting these children in line with Maqasid Shariah principles, including the use of modern tools like DNA testing to adapt Islamic law to contemporary needs. A multidimensional approach involving knowledge, psychology, and legality is essential to safeguard their rights. The hierarchical framework in Maqasid Shariah supports the recognition of biological fathers to ensure the child’s welfare and universal justice. The study argues that MUI Fatwa No. 11 should reflect Maqasid Shariah’s holistic and dynamic principles to align Islamic law with social changes. It asserts that reconstructing the lineage of children born out of wedlock is intended to affirm their inherent dignity (fitrah) as equal to other children, without endorsing adultery or undermining the institution of marriage in Islam. Ultimately, this approach seeks to uphold social justice and universal welfare.